Lean accounting : (John Wiley & Sons, 2007)
Anyone involved in a lean transformation inevitably bumps up against the vagaries of the accounting systems that reward overproduction and waste and seem to punish true improvement. We wonder what would happen if the accountants actually came to the production floor and witnessed firsthand the havoc created by their systems. This volume gathers together some of the best thinkers to take a critical look at traditional cost accounting and defines a path forward to 'lean accounting.